IMPLEMENTASI QAILULAH UNTUK MENINGKATKAN KONSENTRASI BELAJAR SISWA DI SMPIT AL-RIDWAN KARAWANG (STUDI KASUS: SMPIT AL-RIDWAN KABUPATEN KARAWANG - Farhan Abdul Aziz; Ajat Rukajat; Agus Susanto (Alifbata : Jurnal Pendidikan Dasar, 2025)
This study focuses on the implementation of qailulah as a strategy to improve students' learning concentration. The qailulah method is identified as a strategy that is able to overcome the problem of decreased concentration, memory, and students' ability to absorb learning materials. This study was conducted at SMPIT Al-Ridwan karawang. The purpose of this study is: (1) To find out the implementation of qailulah to improve concentration in class VIII A students at SMPIT Al-Ridwan. (2) To find out the supporting and inhibiting factors of qailulah implementation to improve concentration in class VIII A students at SMPIT Al - Ridwan. (3) To find out the impact of qailulah in improving learning concentration in class VIII A students at SMPIT Al - Ridwan.